KINERJA TUTOR DALAM PROSES PEMBELAJARAN PAKET C - Lambok Amran Adrianto (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2010)
The purpose of this research is to obtain empirical data on tutor’s performance in managing instructional activities of Package C Program at Community Learning Activities Center (CLAC). The research was conducted at a CLAC in North Jakarta. The method employed was descriptive method with qualitative approach. The researcher made direct observation to the CLAC where Package C program was being implemented. To obtain valid and reliable data and information, the researcher also conducted in-depth interview. Based on the available data and information, the research concluded that according to the respondents’ opinion all tutors have conducted instructional process in the line with the existing standard procedures. The tutors make a good preparation before instructional process and they are capable enough to perform their tasks professionally. They have a good mastery of the instructional materials and sound ability to use appropriate instructional media to improve participants’ learning achievement. For a better result in the future, the tutors are suggested to be more proactive to develop their knowledge and skills related to their job.